Amphi-functional mesoporous silica nanoparticles for dye separation. Issue 28 (6th July 2017) - Shinde, Pravin; Gupta, Sayam Sen; Singh, Baljeet; Polshettiwar, Vivek; Prasad, Bhagavatula L. V.
Abstract : Synthesis of amphi-functional mesoporous silica nanoparticles (~80 nm) by stepwise chemical modifications of outer and inner pore surfaces and their utilization for the separation of hydrophobic dyes from hydrophilic ones is reported. Abstract : Synthesis of amphi-functional mesoporous silica nanoparticles (∼80 nm) by stepwise chemical modifications of outer and inner pore surfaces is reported. These materials display a clear "Janus" like character and are able to selectively and completely separate hydrophobic dyes form a mixture of dyes. Our results clearly suggest a clear partition of more hydrophobic dyes into the pores from a mixture of two dyes. In addition this material displays a remarkable recycling ability for 10 cycles with up to ∼99% dye removal from water.